Pengaruh Keanekaragaman Manajemen Terhadap Luas Pengungkapan Tanggung Jawab Sosial Perusahaan - Agus Nisfur Romdioni; Ade Sri Ulita (Musamus University, 2019)
This study examines the diversity of management in the disclosure of corporate social responsibility. Management diversity is measured based on gender diversity and national diversity. The population in this study reports mining companies listing on the Indonesia Stock Exchange in 2013-2015 The sample used by 15 companies is based on the purposive sampling method. Data analysis uses multiple regression analysis with the help of SPSS analysis tools. The results of the analysis test show that gender diversity and diversity of foreigners on the board of commissioners and managers influence the level of corporate social responsibility disclosure. This article offers important implications for companies to pay attention to the proportion of management diversity in order to produce good decisions so that companies can report and implement CSR programs on an ongoing and periodic basis. Keywords: CSR, gender, nationality, diversity